(untitled) (Swiss Medical Weekly, 2011)
This prospective, single centre, observational study analysed the rate of catheter related blood stream infections in critically ill patients in intensive care units treated with haemo(dia)filtration. The infection rate was 3.8 per 1000 patient days. All infections were caused by coagulase negative staphylococci. BACKGROUND:Temporary central venous catheters in patients undergoing continuous veno-venous haemo(dia)filtration contribute to serious infectious complications. The goal of this study was to assess the incidence of catheter related blood stream infections in critically ill patients treated with continuous veno-venous haemo(dia)filtration. METHODS:Prospective observational study of all intensive care unit patients treated with continuous veno-venous haemo(dia)filtration by a central venous catheter at the University Hospital Basel. All patients underwent a standardised anti-infective protocol including screening for nasal colonisation with S. aureus on the day of catheter insertion, antiseptic catheter placement technique and daily disinfection of the insertion site followed by local mupirocin application. Catheter related blood stream infection was diagnosed according to standard guidelines of the Center of Disease Control and Prevention. Primary end point was the incidence of catheter related blood stream infection in all intensive care unit patients treated with continuous veno-venous haemo(dia)filtration. RESULTS:From 2003 to 2007 a total of 194 consecutive critically ill patients treated with continuous veno-venous haemo(dia)filtration were investigated. 173 patients (63% men) were suitable for final analysis. Median age was 68.6 years (18.9–87.8). Eight patients (4.6%) had positive blood cultures, six of them had a catheter related blood stream infection (incidence 3.8/1000 catheter days). All infections were caused by coagulase negative staphylococci. The duration of catheter use (p = 0.02) and pre-existing chronic skin disease (p = 0.042) were identified as potential risk factors for catheter related blood stream infection. CONCLUSIONS:The incidence of catheter related blood stream infection in critically ill patients on intensive care units treated with continuous veno-venous haemo(dia)filtration was 3.8 per 1000 catheter days. All catheter related blood stream infections were caused by coagulase negative staphylococci.